Women's view on men's success:In F. Scott Firztgerald's the Great Gatsby and Hamka's Tenggelamnya Kapal Van Der Wijck - Itsna Syahadatud Dinurriyah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2014)
Marriage is a very important step in women’s life. A woman must be sure that the groom she has chosen is the right man for her entirely life, and she must be ready for the consequence of her choice for the rest of her life. Having a handsome, well-known and prosperous husband, is a part of women’s esteem. When all those things gone, it is a condition in which a wife must show her integrity and faith to her husband. In some parts of the world, there is a belief related to the culture that when a woman gets married, she has to set her life as a house wife with high integrity since it is her dignity. She will lose her pride when she decides to be a widow by divorce. The Great Gatsby and Tenggelamnya Kapal Van Der Wijck are the literary works that propose the idea of women’s choice in marriage. They agreed to choose the different men to be their husbands because of the success they see at the time. Both works explore women’s problem when their husbands are not as success as their previous boyfriends. The word ‘choice’ then becomes very important since she cannot take what she has given back because her condition before and after marriage is different.